1997
DOI: 10.1029/96wr03956
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of time domain reflectometry technique using undisturbed soil samples from humid tropical soils of volcanic origin

Abstract: Abstract. Time domain reflectrometry (TDR) isFor calibration, undisturbed soil blocks, with a TDR probe installed in the center, were saturated and then allowed to dry by evaporation. Volumetric water content was calculated from measured K a values and from gravimetric measurements. Because we used undisturbed soil samples, our calibration accounts for the natural heterogeneity in soils. We tested the suitability of various calibration functions relating K a to soil water content for our soils. TDR technique u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 18 publications
8
53
0
3
Order By: Relevance
“…The singular behavior of h in function of P is illustrated in figure 2, which shows the enormous enhance of the radius sampled by TDR probes with a centesimal enhance of P. The theoretical value calculated with P = 0.99 agrees to the assumption of the "radius of the measured soil cylinder" by the TDR probes used in this study (Figure 1). There was also a large degree of agreement between results obtained from experiments conducted by Petersen et al (1995) and Weitz et al (1997) and theoretical values obtained by Knight et al's model to estimate the soil volume by the TDR technique.…”
Section: Probe Orientation and Soil Volume Evaluated By Tdrsupporting
confidence: 73%
See 2 more Smart Citations
“…The singular behavior of h in function of P is illustrated in figure 2, which shows the enormous enhance of the radius sampled by TDR probes with a centesimal enhance of P. The theoretical value calculated with P = 0.99 agrees to the assumption of the "radius of the measured soil cylinder" by the TDR probes used in this study (Figure 1). There was also a large degree of agreement between results obtained from experiments conducted by Petersen et al (1995) and Weitz et al (1997) and theoretical values obtained by Knight et al's model to estimate the soil volume by the TDR technique.…”
Section: Probe Orientation and Soil Volume Evaluated By Tdrsupporting
confidence: 73%
“…The accuracy of θ TDR estimations found by Topp et al (1980) was 0.01 m m -3 . Herkelrath et al (1991) found values of about 0.02 m m -3 , Bohl & Roth (1994) 0.02 to 0.03 m m -3 for mineral soils and 0.03 to 0.07 m m -3 for organic soils, Jacobsen & Schjønning (1995) found a precision in the range from 0.01 to 0.18 m m -3 , and Weitz et al (1997) in the range from 0.02 to 0.52 m m -3 .…”
Section: Soil Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 8-ha site was on a recent alluvial terrace derived primarily from volcanic material (21). The soil (eutric Hapludand) (22) was deep (Ͼ Ͼ4 m) and very well-drained and had high base cation saturation and high capacity to stabilize organic matter and retain P and water (30 -34% by volume of residual water content).…”
Section: Methodsmentioning
confidence: 99%
“…No entanto, os resultados de Rothe et al (1997) indicam que a compactação do solo por ocasião da instalação das sondas pode causar alterações substanciais nas estimativas de umidade pela TDR, principalmente em elevados valores de umidade. Em solos vulcânicos caracterizados pela reduzida densidade e elevados teores de matéria orgânica, Weitz et al (1997) constataram que o modelo proposto por Topp subestimou θ em até 15 %. Malicki et al (1996), utilizando diferentes materiais porosos, inclusive solo, demonstraram que a densidade, assim como a porosidade, influenciam na relação entre Ka e θ e que os erros das estimativas foram contornados quando os efeitos dessas variáveis foram considerados na função de calibração.…”
Section: Introductionunclassified